Investor motivations of a New Zealand biopharma start-up: Angels and crowdfunders. (November 2019) - Miller, Andrea; Scahill, Shane; Warren, Lorraine
The process of funding any start-up can be a complicated process, with a range of options depending on the nature and stage of the enterprise. This article compares the motivations of Business Angels with equity-based crowdfunders of a New Zealand start-up biopharma company, XYZ, who were developing a therapy for a specific disease. The study finds that contrary to previous research, nonfinancial rewards do play a role in crowdfunding investments. Our results are based on a survey, founded on an Investment Motivational Model (4Ps) with components including Philanthropy, People, Product, and Profit.